Pengaruh Supervisi Akademik Kepala Sekolah dan Motivasi Kerja Guru Terhadap Kinerja Guru SMA di Kecamatan Balige Kabupaten Toba Tahun 2025 (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the influence of principal academic supervision and teacher work motivation on the performance of senior high school teachers in Balige District, Toba Regency. Teacher performance is a key factor in achieving educational goals, influenced by external support such as academic supervision and internal factors such as work motivation. The research method employed is quantitative inferential, with a population of 143 teachers from three different senior high schools. The sample, determined using the Krejcie table, comprised 120 respondents. Data were collected using a closed-ended questionnaire consisting of 60 items. The results of data analysis show that principal academic supervision has a positive and significant effect on teacher performance, contributing between 12.5% and 29.0%. Similarly, teacher work motivation also has a positive and significant effect, contributing between 12.3% and 23.8%. Simultaneously, principal academic supervision and teacher work motivation have a significant combined effect on teacher performance, contributing between 21.3% and 36.2%. These findings highlight the importance of effective academic supervision by school principals and the need to enhance teacher motivation in order to support the achievement of optimal performance.